Pengaruh Metode Bercerita Menggunakan Media Pop-Up Book Terhadap Perkembangan Bahasa Anak Usia Dini - Noldiana Natonis; Risnawati Marzuki; Krismiyati Kana; Feren Kituhoma; Ida Oematan; Martheda Paut; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
This research aims to determine the effect of the storytelling method using pop-up book media on early childhood language development at PAUD Efata Liliba, Kupang City. The research uses a quantitative approach. The independent variable is the storytelling method using pop-up book media and the dependent variable is early childhood language development. The research subjects were 10 children aged 5–6 years. The data collection technique uses an instrument in the form of a questionnaire in the form of a storytelling method using pop-up book media and a language development scale. The data analysis technique is simple linear regression. The research results show that the storytelling method using pop-up book media has a positive and significant effect on early childhood language development with a p value = 0.000 (< 0.05) and an R Square of 0.198. This means that the storytelling method contributes 19.8% to children's language development. It is hoped that educators will stimulate children with the storytelling method using pop-up book media which has proven to be effective in increasing children's intelligence, listening, speaking abilities and courage in expressing ideas.